Evaluation of caving mining methods through multi-criteria decision-making: an integrated analytic hierarchy process–analytic network process methodology - Catalan, A; Ferguson, G (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
The increasing scale, depth and complexity of modern cave mining operations have elevated the importance of transparent, auditable and defensible decision-making in cave design and planning. Traditional approaches often rely on expert judgement applied in an informal or weakly structured manner which can obscure assumptions, hide uncertainty, and make it difficult to compare fundamentally different design options or hazard mitigation strategies. In cave mining, risk is fundamentally a function of uncertainty, with lack of knowledge representing the highest level of risk severity; consequently, reliance on comparative financial criteria alone to select alternatives can be misleading where long-term assumptions such as metal prices, discount rates and cost escalation are themselves highly uncertain. This paper presents a novel integrated analytic hierarchy process–analytic network process (AHP–ANP) framework for multi-criteria decision-making in cave mining, applied to the selection of an appropriate caving variant – specifically the comparison of macroblock panel caving versus panel caving. The framework decomposes the decision into a four-level hierarchy of goals, criteria, subcriteria, and technical factors, with rubric-anchored scoring that converts expert judgement into structured, consistent, and traceable ratings. AHP is applied where criteria are hierarchical and largely independent; ANP captures the interdependencies and feedback loops that a pure hierarchy cannot model. Pairwise comparison scores were assigned by a panel of 3 specialists with a combined cave mining experience of approximately 120 years, with all consistency ratios confirmed below the accepted threshold of 0.10. The results demonstrate that macroblock panel caving is primarily profitability-led, with decision sensitivity concentrated in operational delivery and construction enablement, while panel caving is more balanced across knowledge confidence, risk exposure, and profitability. The paper shows that structured decision frameworks substantially support expert judgement and improve its clarity, consistency, and defensibility – particularly for high-impact decisions made under conditions of limited knowledge – while remaining practical for integration into real project environments.
Keywords: block and panel caving; decision-making; multi-criteria decision-making; analytic hierarchy process; analytic network process; acceptability criteria; risk; lack of knowledge; mining alternatives